Analisis Kuantitatif Pemeringkatan Penilaian Bangunan Cagar Budaya di Kabupaten Kulon Progo Provinsi Daerah Istimewa Yogyakarta - Andi Putranto; Syehkhan Dartiko Aji; Jalu Naufal Falah (Badan Riset dan Inovasi Nasional, 2023)
Abstract. Quantitative Analysis for Ranking Assessment of Cultural Heritage Buildings in Kulon Progo Regency, Special Region of Yogyakarta. Many cultural heritage buildings in Kulon Progo Regency can be dated back to the period before and during Indonesia’s colonial period. According to the Law of the Republic of Indonesia Number 11 of 2010 Concerning Cultural Conservation, a building could be categorized as Cultural Heritage if it has passed the registration, assessment, or assessment process, or until authorities may establish its rank. The assessment of cultural heritage buildings is carried out to prepare a recommendation text to designate them as cultural heritage. Therefore, this research tries to re-evaluate cultural heritage buildings using quantitative analysis methods with weighting factors to obtain a final value which produces a ranking of cultural heritage buildings related to aspects of protection, development and utilization while still being guided by preservation principles based on the numbers obtained as final assessment. It is hoped that the results of the assessment using this formula will be used in ranking according to the final value obtained by each cultural heritage building which is closely related to its utilization and development while still being guided by the principles of cultural heritage preservation. The results of this research propose four classes, namely 1) Buildings with low utilization and preservation; 2) Buildings with moderate utilization and preservation; 3) Buildings with high utilization and preservation, and; 4) Buildings with very high utilization and preservation. These four classes are strongly related to the priority level of future handling activities for these buildings if conditions require maintenance, both in terms of protection, development, and utilization. Keywords: Cultural Heritage Buildings, ranking, Kulon Progo, Quantitative Analysis Abstrak. Cukup banyak bangunan cagar budaya yang berasal dari masa prakolonial serta masa kolonial di Kabupaten Kulon Progo. Menurut Undang-Undang Republik Indonesia No. 11 Tahun 2010 tentang Cagar Budaya, bangunan disebut sebagai Cagar Budaya jika telah melalui proses pendaftaran, pengkajian dan dirumuskan dalam naskah rekomendasi untuk ditetapkan oleh pejabat yang berwenang sesuai dengan peringkatnya. Penilaian bangunan cagar budaya dilakukan untuk menyusun naskah rekomendasi dalam rangka penetapannya. Oleh karena itu, penelitian ini mencoba menilai kembali bangunan cagar budaya dengan menggunakan metode analisis kuantitatif dengan faktor pembobot untuk memperoleh nilai akhir yang menghasilkan peringkat bangunan cagar budaya berkaitan dengan aspek pelindungan, pengembangan, serta pemanfaatan dengan tetap berpedoman pada kaidah pelestarian berdasarkan angka yang diperoleh sebagai penilaian akhir. Hasil penilaian dengan formula ini diharapkan akan digunakan dalam pemeringkatan sesuai nilai akhir yang diperoleh tiap bangunan cagar budaya yang berkaitan erat dengan pemanfaatan, pengembangan dengan tetap berpedoman pada prinsip pelestarian cagar budaya. Hasil penelitian ini mengusulkan empat kelas, yaitu 1) Bangunan dengan ketermanfaatan dan kelestarian rendah; 2) Bangunan dengan ketermanfaatan dan kelestarian sedang; 3) Bangunan dengan ketermanfaatan dan kelestarian tinggi, dan; 4) Bangunan dengan ketermanfaatan dan kelestarian sangat tinggi. Keempat kelas ini berhubungan kuat dengan tingkat prioritas kegiatan penanganan ke depannya terhadap bangunan-bangunan tersebut jika terjadi kondisi yang memerlukan penanganan, baik dalam pelindungan, pengembangan, maupun pemanfaatannya. Kata kunci: Bangunan Cagar Budaya, pemeringkatan, Kulon Progo, Analisis Kuantitatif